DFT Study of a Novel Organic Film: The Structural versus Magnetic Effects. (29th November 2015) - Simonetti, S.; Juan, A.; Brizuela, G.; Ulacco, S.
Abstract : Unsaturated fatty acids have great interest by their activities as industrial materials in novel applications. In the present work, the cis-3-hexenoic acid (HA) adsorbed on the Ni(111) surface was studied by first-principles calculations using the Vienna Ab Initio Simulation Package (VASP). The most stable location for HA is presented on top site of Ni(111), although the energies are very similar for all the adsorption sites. The surface-molecule interaction takes place between the carboxyl group of HA and surrounding Ni atoms. The adsorption is weak and consequently the metal-molecule length is enhanced. The carboxyl group is elongated and weakened after adsorption giving rise to a shift in stretching frequencies. There are notable changes on the magnetic moments values of Ni surface atoms neighboring to the molecule that mainly induced magnetic moments on O and H atoms. Noticeable charge transfer occurs in 3d 4s, p Ni orbitals and 2s C, 2s p O, 1s H orbitals of carboxyl group. The surface presents positive work function changes after adsorption as a consequence of an electron back-donation. During interaction, the significance of the magnetic effects over the structural effects is evidenced. This sets the stage for a future adsorption process improvement based on the modification of the surface magnetic properties.